Assessment of the nutritional status of adult in-patients in a tertiary public hospital in Malaysia: a single-day point prevalence study - Gee, Tikfu; Abd Ghani, Nur Suriyana; Nik Hisyamuddin Fathi, Nik Qisti Fathi; Cheong, Jian Liang (Internet Scientific Publications, 2019)
Malnutrition is a major problem that is encountered in day-today clinical practice and is associated with increased risk of morbidity and mortality. Unfortunately, malnutrition is often undetected unless the patient is on the extreme ends of the malnutrition spectrum. Public hospitals in Malaysia have yet to have a standardized protocol for nutrition screening and consensus concerning methods to assess nutritional status is lacking. This cross sectional study endeavours to utilise a simple but yet clinically relevant technique (Body-Mass Index) to perform a one-day survey on the nutritional status of all adult patients admitted to a tertiary public hospital as an initial tool in the diagnosis of malnutrition.